THE FREQUENCY OF HEART RHYTHM DISORDERS IN PREHOSPITAL PHASE OF ACUTE CORONARY SYNDROME - Jasna Milutinović-Puača; Slađana Anđelić (Российский кардиологический журнал)
Prehospital management of patients with acute coronary syndrome (ACS) is the essential element which influences the survival of patients and the outcome of the disease. Most lethal outcomes occur within the first hour after the onset of acute myocardial infarction (AMI), and the usual cause is some of heart rhythm and conduction disorder.Aim. To assess the frequency of each form of ACS, and the incidence of the development of rhythm and conduction disorders during the first 12 hrs in relation to the localization of ACS and disease outcome.Material and methods. We analyzed prospectively 107 patients transported under continual ECG monitoring to the Coronary Unit after ACS diagnosed prehospitally by the team of the Belgrade Emergency Medical Services. AMI localization was detected and the development of rhythm (supraventricular and ventricular), and conduction disorders were followed by prehospital ECG monitoring. Patients’ outcome was under follow-up until discharge from hospital.Results. Acute ST-elevation myocardial infarction (STEMI), both anterior and diaphragmatic, is most frequent in men aged 50–59 years. There were no statistically significant differences in the occurrence of heart rhythm and conduction disorders both in the STEMI and non-STEMI (NSTEMI) groups. The most frequent rhythm disorders during the first 4 hrs after STEMI onset were sinus bradycardia, sinus tachycardia and ventricular tachycardia, while atrial fibrillation and single ventricular extrasystole were most frequent after 5–12 hrs. In STEMI, AV blocks occurred exclusively during the first 4 hrs, while bundle branch blocks occurred statistically more significantly during the first 4 hrs. Sinus bradycardia and atrioventricular blocks were statistically significantly associated with diaphragmatic STEMI. In this localization there were no bundle branch blocks. The most frequent rhythm disorder associated with anterior STEMI was sinus tachycardia that occurred exclusively during the first 4 hrs. The occurrence of ventricular tachycardia and ventricular fibrillation in any of STEMI locations was statistically more significant in the first 4 hrs after complaints onset. In the studied group of patients with ACS mortality rate was 12,1%, while in the group of STEMI patients it was 11%, with a significant frequency of infarction with anterior localization and bundle branch block in men.Conclusion. Future studies should be directed toward identifying methods, as precise as possible, for early screening of heart rhythm and conduction disorders in ACS so as to enable a timely, preventive and therapeutic management.